2010
DOI: 10.1007/s10877-010-9240-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac index measurements by transcutaneous Doppler ultrasound and transthoracic echocardiography in adult and pediatric emergency patients

Abstract: The USCOM-1A hemodynamic monitoring technology showed poor correlation and agreement to standard transthoracic echocardiography measures of cardiac function. The utility of USCOM-1A in the management of critically ill patients remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…However, the measurement of cardiac output is important in EDs and should be considered in future studies on shock. Novel, noninvasive, accurate techniques for its assessment may render this more practical [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the measurement of cardiac output is important in EDs and should be considered in future studies on shock. Novel, noninvasive, accurate techniques for its assessment may render this more practical [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have reported poor agreement of transthoracic and transesophageal echocardiographic measurement of the aortic valve (AV) and pulmonary valve (PV) diameter compared with the morphometrically determined USCOM values. These studies consequently reported poor agreement of echocardiographic, and PAC determined CO values [54, 55]. USCOM's morphometrically calibrated Doppler method is based on height and weight determined AV and PV annular diameters to calculate flow volumes, with the algorithm derived from normal 2D echocardiographic data [56].…”
Section: Discussionmentioning
confidence: 99%
“…It has a short learning curve and has few procedural risks. There is, however, quite a proportion of unobtainable imaging, the proposed valve areas can differ significantly from the truth (specifically in elderly patients, patients who are critically ill, and patients with structural heart disease), and there can be a big difference between the estimated output and the calibrated reference value 3336 .…”
Section: Methods Of Hemodynamic Monitoringmentioning
confidence: 99%